Taqman-based Reverse Transcription and Real-time PCR for Diagnosis of Peste des Petits Ruminants (PPR) /Small Ruminant Morbilli (SRM) Virus from Clinically Affected Animal Samples Collected in Thrissur District, Kerala State and Molecular Epidemiology of Recovered Isolates - Karunakaran, Sunitha; Beena. P. S; Gopinathan, Gopika Thattat; Sasidharan, Hareesh (Innovations in Biological Science Vol. 4, 2024)
Peste des petits ruminants (PPR) is caused by a virus of the family Paramyxoviridae, genus Morbillivirus and species Morbillivirus caprinae or small ruminant Morbilli virus. PPR also known as ovine rinderpest is an acute, highly contagious, World Organization for Animal Health (WOAH) notifiable and economically important transboundary viral disease affecting primarily sheep and goats associated with high morbidity and mortality. Camels and wild small ruminants can also be affected by PPRV. PPR is considered as one of the main constraints in augmenting the productivity of small ruminants in developing countries and severely affects poor farmer’s economies. The disease is clinically manifested by pyrexia, occulo-nasal discharges, necrotizing and erosive stomatitis, gastroenteritis, diarrhea, bronchopneumonia and can be diagnosed from classic clinical signs, pathological lesions, and specific detection of virus antigen-surface proteins/antibodies/viral RNA in the clinical samples by various immune chromatographic/serological tests and molecular assays. The current diagnostic strategy for PPR used in network laboratories of AHD Kerala is mainly based on serological assays. The present study aimed to standardize Taqman-based reverse transcription Real-Time PCR (RT PCR) protocols for the detection of PPR virus in samples like EDTA blood collected during viraemic/febrile phase and tissue samples after post-mortem from clinically affected animals- and to study the molecular epidemiology of isolates recovered targeting Fusion protein (F) gene.